Twofold role of calcined hydrotalcites in the degradation of methyl parathion pesticide - Sampieri, Alvaro; Fetter, Geolar; Villafuerte-Castrejon, María Elena; Tejeda-Cruz, Adriana; Bosch, Pedro (Beilstein Journal of Nanotechnology, 2011)
Methyl parathion (MP) is a very toxic organophosphate pesticide used as a non-systematic insecticide and acaricide on many corps. As MP and its by-products are highly toxic, they have to be retained to avoid pollution of rivers and lakes. Highly efficient sorbents are hydrotalcites (HTs) (or anionic clays). We have correlated the degradation of an aqueous solution of MP at room temperature, with the basicity of the adsorbing materials. It was found that the metal composition of hydrotalcites determines both the surface electronic properties (basic or acidic) and the sorption capacity. Depending on the basic strength, some calcined hydrotalcites can catalyze the transformation of MP to p-nitrophenol (p-NP) and retain its by-products. Such a process has the advantage of being able to be carried out at room temperature and at the pH of the pesticide solution.
Keywords: basicity; hydrotalcite; methyl parathion degradation; mixed oxide; organophosphate; pesticide; water pollution

(untitled) - Olvera-Velona, A.; Benoit, P.; Barriuso, E.; Ortiz-Hernandez, L. (Agron. Sustainable Dev., 2008)

(untitled) - Buratti, F. M.; Leoni, C.; Testai, E. (J. Verbraucherschutz Lebensmittelsicherh., 2007)

(untitled) - Cornejo, J.; Celis, R.; Pavlovic, I.; Ulibarri, M. A. (Clay Miner., 2008)

(untitled) - Mingelgrin, U.; Kljger, L.; Saltzman, S. (Pestic. Sci., 1979)

(untitled) - Mingelgrin, U.; Saltzman, S. (Clays Clay Miner., 1979)

(untitled) - Zeng, Q.-R.; Liao, B.-H.; Yang, B.; Tang, H.-X.; Xue, N.-D. (Biol. Fertil. Soils, 2006)

(untitled) - Cabello, C. I.; Botto, I. L.; Thomas, H. J. (Thermochim. Acta, 1994)

(untitled) - Cavani, F.; Trifirò, F.; Vaccari, A. (Catal. Today, 1991)

(untitled) - Evans, D. G.; Slade, R. C. T. (Struct. Bonding, 2006)

Solid-state Supramolecular Chemistry: Two- and Three- Dimensional Inorganic Networks - Trifirò, F.; Vaccari, A. (Hydrotalcite-like Anoinic Clays (Layered Double Hydroxides), 1996)

(untitled) - Rives, V.; Ulibarri, M. A. (Coord. Chem. Rev., 1999)

(untitled) - Bergada, O.; Vicente, I.; Salagre, P.; Cesteros, Y.; Medina, F.; Sueiras, J. E. (Microporous Mesoporous Mater., 2007)

(untitled) - Li, F.; Duan, X. (Struct. Bonding, 2006)

(untitled) - Paredes, S. P.; Fetter, G.; Bosch, P.; Bulbulian, S. (J. Mater. Sci., 2006)

(untitled) - Rivera, J. A.; Fetter, G.; Bosch, P. (Microporous Mesoporous Mater., 2006)

(untitled) - Yong, Z.; Mata, V.; Rodrigues, A. E. (Ind. Eng. Chem. Res., 2001)

(untitled) - Yong, Z.; Rodrigues, A. E. (Energy Convers. Manage., 2002)

(untitled) - Hibino, T.; Tsunashima, A. (Chem. Mater., 1997)

(untitled) - Olguin, M. T.; Bosch, P.; Acosta, D.; Bulbulian, S. (Clays Clay Miner., 1998)

(untitled) - Bégu, S.; Aubert-Pouëssel, A.; Polexe, R.; Leitmanova, E.; Lerner, D. A.; Devoisselle, J. M.; Tichit, D. (Chem. Mater., 2009)

(untitled) - Park, M.; Lee, C.-I.; Seo, Y. J.; Woo, S. R.; Shin, D.; Choi, J. (Environ. Sci. Pollut. Res., 2010)

(untitled) - Kuśtrowski, P.; Chmielarz, L.; Bożek, E.; Sawalha, M.; Roessner, F. (Mater. Res. Bull., 2004)

(untitled) - Sampieri, A.; Fetter, G.; Pfeiffer, H.; Bosch, P. (Solid State Sci., 2007)

(untitled) - Sampieri, A.; Lima, E. (Langmuir, 2009)

(untitled) - Kovanda, F.; Grygar, T.; Dorničák, V. (Solid State Sci., 2003)

(untitled) - Kovanda, F.; Grygar, T.; Dorničák, V.; Rojka, T.; Bezdička, P.; Jirátová, K. (Appl. Clay Sci., 2005)